The effect of ageing on the surface roughness of varseosmile crown plus and lithium disilicate / Suhaenih Budin - Suhaenih , Budin (2024)
This in-vitro study aims to investigate the effect of artificial ageing on the surface roughness of two groups: 3D printed ceramic-filled hybrid material (VarseoSmile Crown plus) (VSplus group) and milled lithium disilicate glass ceramic (IPS e.max CAD) (Emax group). A total of 20 samples with a sample size of n=10 per group were determined, accounting for a 15% dropout rate. The sample preparation involved fabricating rectangular-shaped samples of both groups with dimensions of 14×12×3 mm. For VSplus (Bego, Bremen, Germany), the samples were 3D printed using a 3D printer (Ackuretta SOL 3D printer), followed by a cleaning process with ethanol in a washing unit (Ackuretta CLEANI) and post-curing under ultraviolet light curing unit (Ackuretta CURIEplus). Meanwhile, the Emax (Ivoclar–Vivadent, Schaan, Liechtenstein) samples were fabricated using a wet dental milling machine (Aidite AMW 400) and sintered in a dental furnace (Ivoclar Vivadent Programat P310) to achieve their final properties. All samples were finished with silicon carbide abrasive papers (Beta 2 grinder-polisher machine, Buehler, Germany) and polished according to the manufacturers' guidelines to achieve a smooth surface. The artificial ageing is done by thermocycling machine (Zecttron Sdn Bhd, Malaysia) to simulate the thermal stresses experienced in the oral cavity. This process involved subjecting the samples to 5000 cycles between temperatures of 5°C and 55°C, with 20secs dwell times and 10secs transfer times. Surface roughness (Ra value) was measured using an optical 3D surface analyser (G4e, Alicona Imaging GmbH, Raaba, Austria) before and after ageing. A representative sample from each group was randomly selected and examined with Field Emission Scanning Electron Microscopy (FE-SEM) (Quanta FEG 450, Thermo Fisher Scientific, Brno, Czech Republic). Paired t-test was used to compare the mean Ra values of each group before and after ageing. Independent sample t-test was used to compare the mean Ra value between the two groups before and after ageing. The results showed a significant increase in surface roughness for both materials after ageing. The mean Ra value for VSplus significantly increased from 0.145 μm to 0.168 μm (p value<0.05), while for Emax, it increased from 0.223 μm to 0.232 μm (p value<0.05). Meanwhile, the comparison of the Ra value between the two groups before and after ageing shows a significant difference (p value<0.05), with the Ra value of VSplus being lesser than Emax, both before and after ageing. However, VSplus exhibit higher changes in mean Ra value before and after ageing, which is 0.023 μm changes in VSplus and only 0.009 μm changes in Emax. SEM images revealed notably increased roughness and microstructural changes in the surface topography of both groups after ageing. The findings of this study suggest that while both groups exhibit increased surface roughness due to artificial ageing, they were able to maintain their surface integrity near acceptable clinical thresholds.